How Turkish-speaking children tackle negation when it combines with modality and (non)factivity in complex sentences - Hendek, Melike. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis explores how Turkish-speaking children interpret negation when it combines with other logical operators, such as (non)factive verbs and epistemic modals. Experiment 1, testing 60 Preschool (mean age: 5) and 30 Elementary School (mean age: 8) Turkish-speaking children investigate how children handle negation when it interacts with the cognitive factive verbs, bil- ‘know’, anla- ‘realize’; emotive factives üzül- ‘be sad’ and sevin- ‘be happy’ and the non-factive verbs düşün- ‘think’ and san- ‘suppose/ believe’ in complex sentences. The results indicate that while Elementary school Turkish-speaking children show a ceiling level accuracy in the interpretation of both factive and nonfactive verbs under the scope of negation, Preschool children experience problems, such as overfactivization of non factive verbs, not being able to attribute false-belief to the attitude holders in the presence non-factive verbs, over-affirmation of negative sentences and paying attention to the truth value of the complement clauses only, in handling negation especially when it combines with non-factive verbs. Experiment 2 explores another logical operator ‘modality’ and how it is interpreted when it interacts with negation. Testing 18 children it shows how challenging the acquisition and comprehension of this interaction is. In particular, the results of Experiment 2 show that Turkish speaking children tend to favor negative strong epistemic reading over negative weak epistemic reading, hence tend to extend the strong reading to weak epistemic modals.
Keywords: Turkish language -- Study and teaching (Elementary); Language acquisition -- Age factors -- Turkey.; Language awareness in children -- Turkey.